Effect Of Sandoricum Koetjape (Buah Sentul) Extracts On Hypocholesterolemic Activity Using 3- Hydroxy-3-Methylglutaryl-Coenzyme A Reductase (Hmgr) Assay - Yeong, Ai Lin (2013)
Sandoricum koetjape, a tropical fruit tree rich in phytochemical terpenoids, was postulated to suppress cholesterol synthesis through inhibition of HMG-CoA reductase (HMGR) activity. HMGR, a rate-limiting enzyme of cholesterol synthesis consists of two domains, N-terminal sterol-sensing domain (residues 1-339) and Cterminal catalytic domain (residues 460-888). This research was designed to study the hypocholesterolemic activity of S. koetjape extract through inhibition of recombinant human HMGR. In this study, the gene fragment encoding the catalytic domain of HMGR was expressed and purified as a recombinant glutathione Stransferase tagged protein. In vitro enzymatic assay revealed catalytic activity based on the kinetic measurements. Methanolic crude extracts of leaves, bark, fruit hull and flesh from S. koetjape exhibit in vitro inhibition activity significantly on the recombinant human HMGR. Bark was found to be the most potent inhibitor with IC50 <5 μg/ml, followed by fruit hull (IC50 = 32.5 μg/ml), leaves (IC50 = 37.6 μg/ml) and flesh (IC50 = 68.3 μg/ml). In summary, all four plant parts of S. koetjape exhibited hypocholesterolemic activity through HMGR inhibition. The promising finding revealed that S. koetjape is a good candidate for further research as a hypocholesterolemic agent.